Potential Biomarkers Associated with Differential Manifestations of Ulcerative Colitis (UC) in Uyghur and Han Population in China - Lu JJ; Maimaiti M; Liu H; Liu WD; Hui WJ; Huang XL; Gao F (Dove Medical Press, 2021)
Jia Jie Lu, Munila Maimaiti, Huan Liu, Wei Dong Liu, Wen Jia Hui, Xiao Ling Huang, Feng Gao Department of Gastroenterology, People's Hospital of Xinjiang Uygur Autonomous Region, Urumqi, Xinjiang Uygur Autonomous Region, People's Republic of ChinaCorrespondence: Feng GaoDepartment of Gastroenterology, People's Hospital of Xinjiang Uygur Autonomous Region, No. 91 Tianchi Road, Urumqi, 830001, Xinjiang Uygur Autonomous Region, People's Republic of ChinaEmail xjgf0991@163.comBackground: Ulcerative colitis (UC) is one of the main subtypes of inflammatory bowel disease (IBD). The incidence of UC in the Xinjiang region is relatively high in China and the manifestations of UC in Uyghur and Han patients are usually differential. This study aimed to identify potential biomarkers of UC.Methods: All miRNA and mRNA were extracted from the tissue samples obtained from participants in Xinjiang. Differential expression analysis was performed on all mRNAs and miRNAs. The target genes of miRNAs were predicted via three databases. The clusterProfiler package was used for GO and KEGG pathway enrichment analysis.Results: Preliminarily, four miRNAs and 15 genes were associated with the differential manifestations of UC in Uyghur and Han patients. Through the co-expression network construction and further screening in more samples, two miRNAs (hsa-miR-141-5p and hsa-miR-378a-5p) and three genes (ARNTL2, CLDN1 and SLC6A14) were found to be more crucial. These 15 genes were enriched in tight junction, NF-κB, and several other pathways.Conclusion: Two miRNAs (hsa-miR-141-5p and hsa-miR-378a-5p) and three genes (ARNTL2, CLDN1, and SLC6A14) associated with the differential manifestations of UC in Uyghur and Han population were identified, which were potential biomarkers.Keywords: ulcerative colitis, miRNA, biomarkers, Uyghur, Han